Hybrid Nanocavity Resonant Enhancement of Color Center Emission in Diamond - Paul E. Barclay; Kai-Mei C. Fu; Charles Santori; Andrei Faraon; Raymond G. Beausoleil (Physical Review X, 2011)
Resonantly enhanced emission from the zero-phonon line of a diamond nitrogen-vacancy (NV) center in single crystal diamond is demonstrated experimentally using a hybrid whispering gallery mode nanocavity. A 900 nm diameter ring nanocavity formed from gallium phosphide, whose sidewalls extend into a diamond substrate, is tuned onto resonance at a low temperature with the zero-phonon line of a negatively charged NV center implanted near the diamond surface. When the nanocavity is on resonance, the zero-phonon line intensity is enhanced by approximately an order of magnitude, and the spontaneous emission lifetime of the NV is reduced by as much as 18%, corresponding to a 6.3X enhancement of emission in the zero photon line.